Manufacture of modern electrochemical sensors based on organic and inorganic nanoparticles and decorated with multi-walled carbon nanopipes - Eteya, Muhaned Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
One of the reasons for the rapid development of electrochemical sensors for nanomaterials is because of the rapid international development and manufacture, a variety of dangerous chemicals are currently being released into the atmosphere in terms of Airborne, water, and solid waste. Thus, a sensitive, robust, and cost-effective sensor network Make very important pollutants from the atmosphere. Significant progress has been made ineffective electrochemical sensors and biosensors platforms for environmental-based applications of nanomaterials. The current review assesses recent trends in developing an electrochemical sensor platform based on the latest nanomaterials such as metallic nanoparticles, metal oxide nanomaterials, carbon nanomaterials, polymers, and biomaterials. Special synthetic methods, properties, integration techniques, specific sensor applications and development prospects for advanced sensor platforms from these nanostructured materials were also highlighted. The great development of nanomaterial-based electrochemical sensor platforms is driving new momentum to develop new technologies to ensure human health and the environment in days gone by nanotechnology has played a crucial role in upgrade biometric sensors. The sensitivity, accuracy, and reproducibility of the biometric sensors have improved greatly due to the incorporation of nanomaterials into their design. In general, nanomaterial-based electrochemical immune sensors improve sensitivity by allowing wider activation with broader surface recognition molecules for biological recognition as well as enhancing the electrochemical properties of the transformer.